2023
DOI: 10.1186/s43042-023-00405-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of TP53 gene Pro72Arg (rs1042522) single nucleotide polymorphism among Egyptian breast cancer patients

Abstract: Background The P53 protein has an essential role in several cellular processes, including DNA repair, apoptosis, and cell cycle arrest. The pathophysiology of many cancer types has frequently been linked to polymorphisms in the TP53 locus. Over 200 single nucleotide polymorphisms (SNPs) have been identified in TP53. However, Pro72Arg (rs1042522) at codon 72, shows contradictory results in terms of cancer risk. In this study, we aimed to determine if the Pro72Arg (rs1042522) SNP in the TP53 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
1
0
1
Order By: Relevance
“…The meta-analysis by Zhang and colleagues showed no statistically significant association between genotypes of rs1042522 and colorectal cancer risk [40]. Ahmed and coworkers in their research, conducted in the Egyptian population, showed that the R allele was more prevalent among breast cancer patients compared to the control group and that it was not associated with disease progression [41]. Data from Basabaeen et al suggested that the PP genotype contributed to an increased risk of chronic B lymphocytic leukemia in the Sudanese population ten times more than the RR genotype [42].…”
Section: Discussionmentioning
confidence: 97%
“…The meta-analysis by Zhang and colleagues showed no statistically significant association between genotypes of rs1042522 and colorectal cancer risk [40]. Ahmed and coworkers in their research, conducted in the Egyptian population, showed that the R allele was more prevalent among breast cancer patients compared to the control group and that it was not associated with disease progression [41]. Data from Basabaeen et al suggested that the PP genotype contributed to an increased risk of chronic B lymphocytic leukemia in the Sudanese population ten times more than the RR genotype [42].…”
Section: Discussionmentioning
confidence: 97%
“…Известно, что изолированное воздействие бенз(а)пирена, а также сочетанное воздействие бенз(а)пирена и вакцинного антигена SARS-CoV-2 в эксперименте in vitro активирует экспрессию гена TP53 (rs1042522) в случае гетерозиготного варианта гена CG и, напротив, угнетает его экспрессию у GG-гомозигот [18]. Кроме того, вариантный GG-генотип гена TP53 (rs1042522) может быть ассоциирован с повышенным риском развития онкопролиферативных процессов [19,20], что особенно важно учитывать в условиях внешнесредового воздействия бенз(а)пирена как вещества с проканцерогенными характеристиками.…”
Section: т а б л и ц аunclassified